Translation of human tissue factor pathway inhibitor-ß mRNA is controlled by alternative splicing within the 5' untranslated region - Ellery, Paul; Maroney, S.; Martinez, N.; Wickens, M.; Mast, A. (2014)
OBJECTIVE - Tissue factor pathway inhibitor (TFPI) blocks the initiation of coagulation by inhibiting TF-activated factor VII, activated factor X, and early prothrombinase. Humans produce two 3' splice variants, TFPIa and TFPIß, which are differentially expressed in endothelial cells and platelets and possess distinct structural features affecting their inhibitory function. TFPI also undergoes alternative splicing of exon 2 within its 5' untranslated region. The role of exon 2 splicing in translational regulation of human TFPI isoform expression is investigated. APPROACH AND RESULTS - Exon 2 splicing occurs in TFPIa and TFPIß transcripts. Human tissue mRNA analysis uncovered a wide variability of exon 2 expression. Polysome analysis revealed a repressive effect of exon 2 on TFPIß translation but not on TFPIa. Luciferase reporter assays further exposed strong translational repression of TFPIß (90%) but not TFPIa. Use of a Morpholino to remove exon 2 from TFPI mRNA increased cell surface expression of endogenous TFPIß. Exon 2 also repressed luciferase production (80% to 90%) when paired with the ß-actin 3' untranslated region, suggesting that it is a general translational negative element whose effects are overcome by the TFPIa 3' untranslated region. CONCLUSIONS - Exon 2 is a molecular switch that prevents translation of TFPIß. This is the first demonstration of a 5' untranslated region alternative splicing event that alters translation of isoforms produced via independent 3' splicing events within the same gene. Therefore, it represents a previously unrecognized mechanism for translational control of protein expression. Differential expression of exon 2 denotes a mechanism to provide temporal and tissue-specific regulation of TFPIß-mediated anticoagulant activity. © 2013 American Heart Association, Inc.